Avant-garde: The Convulsions of a Concept - Michael T. Jones (Studies in 20th & 21st Century Literature, 1980)
The current status of the «avant-garde» provokes many questions, which include both inner-artistic matters and matters of history and society commonly associated with Marxist or reception-oriented thinkers. The convolution of questions cannot be disentangled; efforts to confront the dilemmas of the avant-garde cannot abstract from matters of commodification, recent reception, or the complex dialectic of «classical» and «modern.» The essay deals with the most recent manifestations of avant-garde aesthetic impulses. It emphasizes the historical and social aspects of German theorizing in contrast to purely formalist or ahistorical conceptions commonly found elsewhere. It insists that such «materialist» theory does greater justice than formalist conceptualizations to the proverbial connections of «art» and «life.» It tries to integrate the present phenomenon of proliferating theory into the theoretical exposition, as a characteristic trait of the current situation. It warns against abandoning the subversive content of classical modernism in the course of developing a theory of post-modernism.
Keywords: avant-garde; history; society; Marxist; Marxism; commodification; recent reception; classical; modern; historical; social; German; German literature; formalist; ahistorical; materialist; art; life